VD_FINDINFO HC / 2012 / 495 vom 8. August 2012 - VD Tribunal cantonal (2012)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, TRANSACTION JUDICIAIRE | 117 let. b CPC (CH), 309 let. a CPC (CH), 319 let. a CPC (CH), 320 CPC (CH), 322 al. 1 CPC (CH), 326 CPC (CH), 337 CPC (CH), 339 al. 2 CPC (CH), 341 CPC (CH)